One Way Ticket to a Penal Colony: North American Political Prisoners in Van Diemen’s Land - Carter, John (Ontario History)

(untitled) (The Ontario Historical Society, 2009)
This article will focus on the plight of ninety-three English speaking, North American political prisoners who were given a one-way ticket and ended up in the Van Diemen’s Land penal system, as a result of their involvement in the incursions into Upper Canada and the associated rebellious acts committed in 1838. The end of rebellion in Canada was the beginning of experiences significant to the historical record in Australia. The capture, incarceration and transportation of Patriot exiles to Van Diemen’s Land and the stories of their imprisonment, release and repatriation form an intriguing episode in Australia’s and Canada’s twinned heritage.